URGENSI LITERASI DIGITAL BAGI WIDYAISWARA - Ranti Nuranita; Dedi Restendi (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2021)
The digital era is marked by the shift of mechanical and analog technology to digital technology. The transfer of technology has led to the disruption of human culture. One of them is in the way of thinking and acting, especially for professionals. Today, a professional must have digital literacy competence, namely the ability to access, manage, understand, integrate, communicate, evaluate, and create information safely and precisely through digital technology. Widyaiswara is a related profession. Questions arise related to this, namely, "Why must digital literacy be mastered by widyaiswara, and for what?" A literature review has been conducted on ten journal articles published in Google Scholar to answer these questions. The results of the study concluded that digital literacy competence could answer the challenges of training in terms of the ability to update information, use gadgets and applications as sources of information, process and present information from training teaching materials, and finally, take an essential role in facing the pattern of distance training implementation based on e-learning application with its various sophistications. The results of the review are expected to provide insight and can be used as literature for further research.